WHAT’S IN THE ADVERTISEMENT? TOWARD LANGUAGE LEARNING AND BEYOND - Amporn Sa-ngiamwibool (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2012)
Advertisements are valuable tools for ESL/EFL classrooms. Many instructors, however, tend to focus on enhancing language learning per se. With an experimental way, they are tools for discussions and analyses of contemporary cultural issues. To utilize the mass media in the classrooms, CLL and project work are suggested to be effective tools for this. The main purpose of the study was therefore to explore whether CLL and project work were effective for enhancing the discussions and analyses of cultural issues in Thai advertisements. The results of the study revealed that, cognitively and culturally, some advertisements provided a stimulating approach to discussions and analyses of the cultural issues since their contents contained highly cultural insights of the issues which provided topics for discussions and analyses. Communicatively, the discussions enhanced more active roles among the group communication, group interaction and dynamics, and communication skills. Linguistically, the discussions improved their speaking and writing skills. Pedagogically, the increased skills enhanced their L2 learning. This study, however, limits to a Thai EFL classroom and monocultural society. The replication with other EFL classrooms and in plural and intercultural societies is needed. Keywords: advertisements, cultural discussion, CLL, project work teaching